Comparison Of The Application Of Flipchart Media And A Combination Of Flipchart - Video Media Towards Mastering Knowledge And Attitudes Regarding Stunting In Pregnant Women In Sukoharjo Village, Wilangan District, Nganjuk District - Lutfiani, Tsania Ulfa (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Preventing the risk of stunting requires efforts to increase knowledge and attitudes among pregnant women. One very effective effort to support knowledge change is outreach using flipcharts and video media. The aim of this research is to analyze the comparison of the application of flipchart media and flipchart-video combination media on the mastery of knowledge and attitudes about stunting in pregnant women in Sukoharjo Village, Wilangan District, Nganjuk Regency. This research design uses a quasi-experimental study with a study nonequivalent kontrol group design. The population in this study was 30 pregnant women who were divided into 2 groups. The results of the analysis using the Mann Whitney Test showed a significance value of 0.251>0.05 for knowledge and 0.018>0.05 for attitude. The results of this study indicate that the use of flipchart media and flipchart-video combination media provides the same increase in knowledge about stunting in pregnant women, and the use of flipchart media and flipchart-video combination media provides a difference in increasing attitudes about stunting in pregnant women in Sukoharjo Village. Wilangan District, Nganjuk Regency.